Neu3CA-RT: A framework for real-time fMRI analysis. (30th December 2018) - Heunis, Stephan; Besseling, René; Lamerichs, Rolf; de Louw, Anton; Breeuwer, Marcel; Aldenkamp, Bert; Bergmans, Jan
Highlights: Real-time fMRI is an increasingly useful tool in the field of psychoradiology to gain an understanding of real-time brain network changes and to provide insight into real-time data quality. Neu 3 CA-RT is a new, Matlab- and SPM-based rtfMRI framework that allows real-time fMRI image transfer, (pre)processing and analysis. Dynamic fMRI images can be mapped to a basis set of spatial brain networks (iCAPs) and correlated with a set of 50 behavioural profiles from the BrainMap database. Experimental results support a working proof of concept that requires further development. Abstract: Real-time functional magnetic resonance imaging (rtfMRI) allows visualisation of ongoing brain activity of the subject in the scanner. Denoising algorithms aim to rid acquired data of confounding effects, enhancing the blood oxygenation level-dependent (BOLD) signal. Further image processing and analysis methods, like general linear models (GLM) or multivariate analysis, then present application-specific information to the researcher. These processes are typically applied to regions of interest but, increasingly, rtfMRI techniques extract and classify whole brain functional networks and dynamics as correlates for brain states or behaviour, particularly in neuropsychiatric and neurocognitive disorders. We present Neu 3 CA-RT : a Matlab-based rtfMRI analysis framework aiming to advance scientific knowledge on real-time cognitive brain activity and to promote its translation into clinical practice. Design considerations are listed based on reviewing existing rtfMRI approaches. The toolbox integrates established SPM preprocessing routines, real-time GLM mapping of fMRI data to a basis set of spatial brain networks, correlation of activity with 50 behavioural profiles from the BrainMap database, and an intuitive user interface. The toolbox is demonstrated in a task-based experiment where a subject executes visual, auditory and motor tasks inside a scanner. In three out of four experiments, resulting behavioural profiles agreed with the expected brain state.